Burnout Prevention Efforts for Healthcare Professionals in Hospital that Server COVID-19 Patients During Pandemic - Liana, Duta; Dwijayanti, Fifi; Fauziah, Nuraini; Lestari, Dewi (Alta Dharma Publisher, 2024)
Background: COVID-19 pandemic has become main workload issue for health workers in hospitals. Pandemic period requires health workers to endure working under stressful conditions and exposure infection risks. Continuous and uncontrolled stress causes burnout. Objective: It aims to determine prevention efforts in workplace that influence on burnout. Methods: It was cross-sectional study in six hospitals. Population are HCPs consisting of doctors, nurses, pharmacists, nutritionists, medical laboratory personnel, and radiographers. It used primary data based on Copenhagen Burnout Inventory (CBI) questionnaire combined with questionnaire refers to Health Minister No.HK.01.07/MENKES/1591/2020 regarding burnout prevention efforts. Analysis with univariate and bivariate with chi-square test to determine relationship between characteristics and prevention efforts to burnout incidence. Research has passed ethical review from Lavalette Hospital. Results: The result was obtained from 318 respondents from six hospitals. Most respondents were women (76.4%), married (77.7%), had worked ?6 years (56.0%) and nurses (63.5%). Individual prevention has relationship with personal, work-related, and patient-related burnout. Group prevention has a relationship with work-related and patient-related burnout. Organizational prevention has relationship with personal, work-related, and patient-related burnout (p<0.05). Conclusion: Prevention efforts for individuals, groups, and organizations are related to burnout. Individual prevention influences work-related burnout, and professions influence personal and work-related burnout. The results can be used as a reference for providing appropriate and effective burnout prevention interventions through individual, group, or organizational prevention